Self-efficacy, Self-Esteem, Locus of Control, and Their Influence on the Performance of Village Officials - Agusman Aris, Affandy; Yahya, Muh.; Wardhana, Aditya; Rachmawaty; Hartini (Jurnal Manajemen, 2024)
This study aims to determine and analyze: the effect of self-efficacy, self-esteem, and locus of control on the performance of village officials; the effect of self-efficacy on the performance of village officials; the effect of self-esteem on the performance of village officials; dan the effect locus of control on the performance of village officials. This type of research is quantitative research with expost facto approach. This research was conducted in Sub-districts Kindang. The population in this study were all village officials totaling 93 people. The sample of the study was 48 peoples. Data collection techniques using questionnaire and documentation techniques. Data analysis techniques are carried out after data from all respondents or other data sources are collected with analytical activities including test prerequisite analysis and hypothesis testing (multiple linear regression). The results of the study show that: overall, self-efficacy, self-esteem, and locus of control had a positive and significant effect on the performance of village officials; self-efficacy had a positive and significant effect on the performance of village officials; self-esteem had a positive and significant effect on the performance of village officials; and locus of control had a positive and significant effect on the performance of village officials.